Influence of altitude on distribution of native palm species :a case study at Gunung Jagoi, Bau, Sarawak - Meni, Anak Manggat (Universiti Malaysia Sarawak (UNIMAS), 2012)
Gunung Jagoi is located in Bau, Sarawak and 35 km from Kuching city. Sufficient information on plants including palm is important for better management and conservation of Gunung Jagoi as community reserve area. Palm species is likely to be varied in each altitude. A study using 10 m × 10 m plot method was carried out to determine the whether altitude influences the distribution of native palm species in Gunung Jagoi, Bau. 9 main plots have been established in each altitude level. There were 21 palm species recorded in Gunung Jagoi, Bau. These species belong to the genus Arenga, Calamus, Caryota (not recorded in medium altitude), Daemonorops, Korthalsia, Licuala, Oncosperma, Pinanga and Salacca (only recorded in low altitude), accordingly. Pinanga Crassipes is dominant species in high and low altitude while dominant species in medium altitude is Licuala petiolulata. Diversity of palm species in all altitudes is low. However, palm species most diverse in medium altitude. The altitude did not influence the palm distribution in Gunung Jagoi, Bau.